Analysing students' perception on the effective tutors using fuzzy set of group decision making - Raziana Che Aziz; Chiam , Chooi Chea (2008)

(untitled)
This study is carried out to analyse learners' perception of effective tutors in Open University Malaysia (OUM) based on various criterion that we have identified. We analysed their perception using method known as Fuzzy Set of Group Decision Making Model. This method usually conducted in a multi-criteria environment, which mostly dependent on the subjective judgment of decision makers and is influenced by the uncertainty and vagueness of each individual preference. The model is proven suitable for quantifying imprecise information, reasoning and decision making based on vague data. This study aims to provide OUM an insight look and further knowledge on the attributes of effective tutors. It can be used as a rule of thumb when appointing external tutors. Effective tutors are vital in enhancing and achieving the objectives of teaching and learning process. The findings show that the proposed evaluation model allows decision makers to express their opinions about tutors' performance by using a more realistic qualitative and fuzzy decision making. It is a suitable tool that can assist decision makers to better evaluate tutors in order to select suitable and effective tutors so that teaching and learning process can takes place. (Authors' abstract)